A preliminary study on graduate employability among Islamic banking and finance graduates: the role of career edge and digital literacy - Abd Rahmali, Nur Atiqah; Jaafar, Mohamad Nizam; Nurazree, Mahmud; Norhasimah, Shaharuddin (UiTM Cawangan Johor, 2025)
Technology has significantly shifted modern workforce skills requirements. There has been growing concern in recent years about the underemployment situation in Malaysia, especially in the case of Islamic Banking and Finance (IBF) graduates who are employed in semi-skilled or clerical sectors despite their skills and qualifications. This divergence signifies a significant barrier to the nation’s economic aspirations. However, while there have been numerous studies on the subject of employability, the area of digital transformation related to IBF graduates has not received sufficient attention. Guided by the CareerEDGE framework which conceptualises employability as a function of career development learning, experience, degree subject knowledge, generic skills, and emotional intelligence with the mediating factor of self-efficacy. A structured questionnaire was provided and a pilot study with 31 recent IBF graduates was conducted. Internal consistency across items was analysed using SPSS version 27. Reliability results indicate solid internal consistency, with Cronbach’s Alpha values exceeding suggested thresholds. Discriminant validity and Pearson correlation analyses further confirm the construct stability and theoretically consistent associations. Although mediation testing is not performed due to the limited pilot sample, preliminary correlations suggest meaningful links between CareerEDGE predictors, digital literacy, and employability. These findings demonstrate that the measurement instrument is robust and ready for full-scale data collection, where structural modelling will be used to examine direct and indirect pathways, including the mediating role of self-efficacy.